Non-timber Forest Products, Their Vulnerability and Conservation in a Designated UNESCO Heritage Site of Arunanchal Pradesh, India - Kaushalendra Kumar JHA (Notulae Scientia Biologicae, 2015)
The Apatani, non-nomadic tribe, have evolved an ecologically sustainable system of rural forestry in Ziro Valley, a proposed heritage site of UNESCO. They have been using non-timber forest products (NTFPs) grown in homestead and nearby forests for a very long period. The present study was aimed at identification of priority NTFPs and uses, their availability status and availability trend, conservation need, and sustainability interventions. Qualitative methods of research like, exploratory survey, questionnaire survey, focus group discussion, semi-structured interview of key informants, etc. were employed for data collection. The Apatani used 112 priority NTFPs for food supplement, herbal medicine, house building material and other purposes. However, on the basis of ecological importance such NTFPs were categorized as very low, low, moderate, high, and very high vulnerable species. Twenty vulnerable species like Antiitari ayi (Actinidia callosa), Biiling (Choerospondias axillaris), Henchi (Rubus niveus), Jojuru ayi (Coccinia grandis), Ngiilyang Khiiko (Centella asiatica) etc. should be conserved and seventeen not vulnerable species at this stage like, Padii hamang (Cardamine hirsute), Sankhe (Quercus griffithii), Bije (Phyllostachys manii), Hiigu hamang (Oenanthe javanica), Kiira (Quercus dealbata ), etc. could be commercialized. However, a balance needed to be struck between commercialization and conservation by adopting a comprehensive policy based on scientific and traditional Apatani knowledge for harvesting and regeneration of NTFPs. Homegardening or community farming is recommended for sustainable supply of commercially important species to be domasticated.